Pengaruh Strategi Manajemen Sumber Daya Manusia terhadap Kinerja Karyawan pada PT. Asuransi Syariah Al-Amin Medan - Nurul Hasanah (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
This study aims to find out and analyze human resource management in improving employee performance. The research approach carried out in this study is descriptive qualitative of the author using a SWOT analysis. This analysis is a systematic identification of factors for formulating a corporate strategy. Then to find out the results of the analysis of employee performance improvement strategies using the IFAS and EFAS matrices, important factors can be identified both from the internal environment and the external environment which are strengths, weaknesses, opportunities, and threats from improving performance. The results of the analysis are obtained from growth or growth-oriented strategy, this strategy indicates the state of the company that is strong and able to continue to develop by taking the opportunities and opportunities that exist to achieve maximum turnover. This strategy was chosen because the calculation result is in square I where the total weighted score of weakness strength is 2.87 while the threat odds are 1.42. The position on this square is very advantageous and can be applied to the maximum. Employee performance can be improved by compensation given in the form of enthusiasm, willingness, and thoroughness of employees to be focused and disciplined. A motivated employee will be more enterprising and disciplined to work, while an unmotivated employee will show discomfort towards his work resulting in the company's goals not being achieved. But at PT. Asuransi Syariah Al-Amin Medan has regular performance carried out by human resource management with Electronic Performance Management appraisal.